0115 Ok google glass – obtaining a new technology. (2nd November 2015) - Gay, Christopher; Graby, Matthew; Charlton, Olivia; Riby, Stuart
Abstract : Background/context: Google Glass made headlines when released in April 2013. The 'connected' headset with embedded 'heads up display' quickly found applications in the healthcare world and became a worldwide technological status symbol due to costing over £1000 and only being available from the United States. The HILS Technical Team pursued obtaining Google Glass long and hard, with several setbacks, but though hard work, convincing pitches and determination eventually acquired one. Description of innovation or topic: The HILS Technical team saw opportunities that other clinical staff may not have, and wanted to pursue improvements in training that were born from inside the team, rather than simply assisting with other people's projects. Our innovation would be to procure, implement and evaluate a new technology of our own choosing. Improvements/outcomes (anticipated or recorded): We expect our improvements to be in two areas- To have introduced a new technology into training, making an improvement to the level of engagement in simulation activity. To have initiated a full cycle of investigation, procurement, implementation and evaluation from within the team, building the knowledge and confidence to direct our expertise to other such projects in the future. Take home messages: That technical members of staff can contribute in more ways than typically thought of That with determination and persistence one can reach their goals Domestic technology can have healthcare implications